2019
DOI: 10.3390/ma12142306
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations of Atomic Diffusion during the Al–Cu Ultrasonic Welding Process

Abstract: Ultrasonic welding (UW) is an important joining technique in the electrical industry. Molecular dynamic simulation has been shown to possess several advantages for revealing the evolution of the atomic-scale structure and the interpretation of diffusion mechanisms at the microscopic level. However, voids associated with the understanding of microstructure evolution in the weld zone and dynamic processes that occur during ultrasonically welded materials still exist, and no UW studies at the atomic scale have so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…8 Temperature evolution history dependent on the sliding velocity sliding velocity for each crystallite inclination angle. This is in good agreement with the results of the work by Yang et al [62], who introduced the diffusion process between dissimilar metals (Al and Cu) as a result of shear plastic deformations and not only the interfacial heat generation.…”
Section: Resultssupporting
confidence: 92%
“…8 Temperature evolution history dependent on the sliding velocity sliding velocity for each crystallite inclination angle. This is in good agreement with the results of the work by Yang et al [62], who introduced the diffusion process between dissimilar metals (Al and Cu) as a result of shear plastic deformations and not only the interfacial heat generation.…”
Section: Resultssupporting
confidence: 92%
“…As a result, diffusion coefficient can be increased by several orders of magnitude [44,45]. Besides, it is reported that volume diffusion can be further accelerated by the ultrasonic force field [46,47]. The much larger diffusion coefficient offers kinetic requirement for fast sintering.…”
Section: Hardness Of the Sintered Aluminum Specimensmentioning
confidence: 99%
“…Since, in the present study, MD simulation has been carried out with scenario 1, wherein actual FSSW condition there will be no relative sliding motion will occur. The MD simulation of Al-Cu Jingwei et al, mentioned few non-FCC phases were formed during the ultrasonic welding, but their study on the non-FCC phases is not detailed further 17 . The current research focused on the interaction between Al and Cu materials atoms during FSSW condition in the solid-solid interface using numerical modelling and MD simulation for microanalysis.…”
Section: Introductionmentioning
confidence: 99%
“…The MD simulation has been carried out with scenario 1 because, in the actual FSSW condition, there will be no relative sliding motion between Al and Cu. Moreover, the study also focuses on the formation of non-FCC phases that have not been detailed in earlier literature 17 .…”
Section: Introductionmentioning
confidence: 99%